ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA PERSAMAAN DAN PERTIDAKSAMAAN LINEAR SATU VARIABEL - Yeti Jumiati; Luvy Sylviana Zanthy (IKIP Siliwangi, 2020)
This research aims to describe the mistakes of students in solving mathematical story problems, by using an indicator of concept errors, principle errors and operating errors. The subject of the study was the 8th grade students of Islamic Junior high school Daarul Fikri. The method used in this study is descriptive qualitative. Research and data collection using test and interview methods. The results of the sudy show that the mistakes made are concept errors where the subject cannot understand the concept of variables, the subject does not write an example and an error in translating the problem into a mathematical model. So that if a concept error is done automatically a principleerroe and an operation error must be made and the problem cannot be further analyzed because the subject cannot write the form of theequation so that the problem cannot be solved correctly.